Meningkatkan Kreativitas Siswa Melalui Model Project Based Learning (PjBL) pada Materi Bangun Datar di Kelas 4 SDN Ngaglik 01 Batu - Resti Wahyu Mutiaradifa; Kartikasari Kartikasari; Alfiani Athma Putri Rosyadi (Reforma : Jurnal Pendidikan dan Pembelajaran, 2023)
In mathematics learning, students often complain that the discussion of material is difficult and requires concrete discussion, especially on flat material. The problem is that learners do not understand what they have learned and how that knowledge is used. A formula that takes a long time is needed to lift the creativity of students to a higher level. Lacking models, it is difficult to facilitate learner learning. So that teachers can develop learning, one of which is with the PjBL learning model. This research is a type of classroom action research (PTK). Is research applied to teaching and learning activities in the classroom that aims to improve the learning process. This research improves the learning model applied in the classroom and increases student learning creativity. Research data sources use primary and secondary data sources. The data obtained are observational data, questionnaires, interviews and documentationThe percentage results show that from cycle I to cycle II there has been an increase in results in the form of values from LKPD that have been done by students with the context of assessment on the creativity of divergent thinking from the results of making compositions and decompositions of various flat buildings with more than one. The results are assessed by the teacher based on the ability of learners to make compositions and decompositions of various flat shapes with more than one. The author innovates by using learning models so that teachers can provide meaningful feedback rather than abstract and vague assessments, allowing students to participate in assessing their own work, learning from their mistakes, and how to solve problems according to the syntax of the project based learning (PjBL) learning model